Temporary changes in STI & HIV testing & diagnoses across different phases of the COVID-19 pandemic, Chicago IL - Pyra, Maria; Schafer, Tommy; Rusie, Laura; Houlberg, Magda; Thompson, Hale M.; Hazra, Anu (Frontiers in Reproductive Health, 2023)
Introduction While the U.S. has seen a sustained rise in STI cases over the past decade, the impact of the COVID-19 on STIs and HIV is unclear. Methods To examine the short- and medium-term impacts of COVID-19 and HIV and STI testing and diagnosis, we compared pre-pandemic trends to three periods of the pandemic: early- pandemic, March-May 2020; mid-pandemic June 2020-May 2021; and late-pandemic, June 2021-May 2022. We compared average number of monthly tests and diagnoses, overall and by gender, as well as the monthly change (slope) in testing and diagnoses. Results We find that after decreases in average monthly STI and HIV testing and diagnoses during the early- and mid-pandemic, cases were largely back to pre-pandemic levels by the late-pandemic, with some variation by gender. Conclusion Changes in testing and diagnoses varied by phase of the pandemic. Some key populations may require additional outreach efforts to attain pre-pandemic testing levels.